2022
DOI: 10.1029/2021ja029669
|View full text |Cite
|
Sign up to set email alerts
|

On the Occurrence of Magnetic Reconnection Along the Terrestrial Magnetopause, Using Magnetospheric Multiscale (MMS) Observations in Proximity to the Reconnection Site

Abstract: Observations at the reconnection site from the Magnetospheric Multiscale mission are used to examine the occurrence of magnetic reconnection along the magnetopause in relation to both the upstream interplanetary magnetic field (IMF) orientation and local magnetosheath variations. While there is a statistically larger number of reconnection intervals observed downstream of the quasi‐parallel bow shock than is accounted for based on the histogram of overall IMF orientations, it is surmised that increased fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 99 publications
1
9
0
Order By: Relevance
“…If there are multiple instances of |ΔV L | > 70 km/s within the 10 min period, then the interval which has the highest peak of ΔV L is checked for the presence of a jet. The methodology to identify jet reversals is based on the methodology developed by Trattner, Burch, et al (2017) and used in previous statistical studies (Petrinec et al, 2022;Trattner, Burch, et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…If there are multiple instances of |ΔV L | > 70 km/s within the 10 min period, then the interval which has the highest peak of ΔV L is checked for the presence of a jet. The methodology to identify jet reversals is based on the methodology developed by Trattner, Burch, et al (2017) and used in previous statistical studies (Petrinec et al, 2022;Trattner, Burch, et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…This enhancement, known as a reconnection jet, is an indication that reconnection is occurring nearby. Enhanced ion velocities with switching directions are called jet reversals, and are evidence of an X‐line nearby the spacecraft position (e.g., Cowley, 1982; Dunlop et al., 2011; Gosling et al., 1982; Paschmann et al., 1979; Petrinec et al., 2022; Pu et al., 2007; Trattner, Burch, et al., 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tests using over 300 MMS magnetopause crossings early in the mission showed that the model predicted the location of the reconnection X‐line within ±1 R E with approximately 85% accuracy (Petrinec et al., 2016; Trattner et al., 2017a, 2017b; Trattner, Fuselier, et al., 2021; Trattner, Petrinec, & Fuselier, 2021). This model is valid even for MP motion not associated with the erosion of the magnetopause by reconnection; such as motion due to changes in the dynamic pressure, fluctuations downstream of the quasi‐parallel bow shock, and rotations in clock angle (Fuselier et al., 2023; Petrinec et al., 2022; Russell et al., 1997).…”
Section: Methodsmentioning
confidence: 99%